Naming diplomacy in football: The case of SPAIN-Kosovo (2020-2024) - Gutiérrez-Chico, Fernando; González-Fuente, Iñigo; Pulleiro Méndez, Carlos (Historia y Comunicación Social, 2024)
Spain and Kosovo faced each other in the qualifiers for the Qatar 2022 World Cup. This was a new challenge for Spain to balance its non-recognition of Kosovo’s statehood and FIFA/UEFA’s norms. Madrid suggested to management the naming in order to avoid the terms "Kosovo/Republic of Kosovo". Thus, how did the Spanish FA apply this policy during and after the qualifiers for the 2022 World Cup? The content analysis of its two main communication channels (web and Twitter) shows a differential, although inconsistent, use towards Kosovo in the first phase. It gets gradually normalised in the post-qualifiers phase. Accordingly, naming as a political weapon becomes a back-and-forth issue whereby the capacity of sporting-diplomatic mobilisation makes the difference.
Keywords: Spain; football; Kosovo; naming; institutional communication